Pengaruh Preservasi Terhadap Nilai Ekonomi Lahan (Kasus: Kota Tua Jakarta) - Kunti Handayani (The Institute for Research and Community Services, Institut Teknologi Bandung, 2003)
Preservation is a mean to maintain the physical heritage which has historical and aesthetical value. Development or modification of preserved buildings in historical district in England and USA gives economic effect, which is reflected through the economic value of land. It is assumed that government intervention can control the economic value of land through the designation of preservation districts. Oud Batavia as a research case is one of historical heritage districts in old town Jakarta which has prime price of land at present. Yet, it is not influenced bay heritage value of preservation program. The government of Jakarta draws up the land price based on the fluctuation of the market price, which is still higher than the neighborhood existing condition. The land price in historic heritage of Out Batavia does not seem to have positive correlation with the perception of the people in determining the land value. It abandons the government rules, the design of the buildings, and it remains only as romantic memories of an old town. What will happen next depends on people's consciousness to maintain Oud Batavia from becoming a deadly zone due to the land economic value